Use of omic heating technology in the process of processing fruits and vegetables. Overview of the subject field - L. Ch. Burak; A. N. Sapach (Пищевые системы, 2024)
The modern consumer prefers natural products with minimal processing, which allows maximum preservation of the nutritional value of the product and fresh taste and aroma. The purpose of this article is to review the results of studies concerning the effect of ohmic heating on the product in comparison with heat treatment and considering the combined use of this method with non-thermal technologies in the production of canned fruit and vegetables. The material for this study was 105 scientific publications. A search for scientific literature in English and Russian on the use of the ohmic heating technology in the process of processing fruits and vegetables was carried out in the bibliographic databases Scopus, Web of Science, as well as in other sources. The period 2010–2023 was adopted as the time frame for the review of scientific publications. To review the subject field of the study, an algorithm was used in accordance with the PRISMA protocol. A scientific search and review of scientific publications on the research topic showed a limited number of studies assessing the ohmic heating (OH) technology in the processing of fruits and vegetables. In the process of using this technology, electric current is applied, ensuring uniform and rapid release of heat inside the food matrix. OH has a shorter processing time, which helps preserve the organoleptic quality of the product and its nutritional value. Compared to heat treatment, the OH technology not only inactivates microorganisms and food enzymes, but also prevents overheating, which reduces the negative impact of temperature on the chemical composition of the product. Evaporation/concentration, dehydration/drying of fruit juices or purees using OH resulted in higher energy efficiency and reduced processing time compared to traditional processing methods. Despite many advantages, there are limitations to large-scale industrial application of the OH method, including corrosion of the electrodes, which can have a negative impact on the product, as well as uneven heating of some types of fruit and vegetable raw materials during continuous processing. The results of this review can be used in the process of conducting further scientific research, which is advisable to continue in order to determine specific processing parameters and eliminate uneven heating of food raw materials.